Postmortem Interval Estimation Time from Algormortis Temperature of Rats Expressed by MARS Model Approach - Syabani, Dwi M.; Eliyani, Hana; Suharsono, Suharsono; Rantam, Fedik A.; Ma’ruf, Anwar (KnE Life Sciences, 2017)
Estimation of Postmortem is one of the challenges in forensic science. The aim of this study was to construct a MARS model of Postmortem interval estimation time (PMT) from algor mortis temperature in Rat. Sixteen healthy male rats (Rattus norvegicus), onemonth old and weigh 100 gram were randomly divided into two groups (eight/each group) and were acclimated respectively among the ambient room (temperature over 28ºC) and at the conditioning room (temperature over 20ºC). The animals then were sacrificed in two days (four rats/day for each divided room) then algor mortis by rectal temperature were recorded after death at 0 and 2,4,6,8, 10,12, 14,16, 18,20 till 22 h respectively. The MARS model is nonlinear regression but performed as a multilinier curve that can have splines fitting and be defined as function model Y = 35.321 + 1.253 * BF1 + 0.436 * BF2 - 1.319 * BF3; and on 20ºC condition room as Y = 29.980 + 1.354 * BF1 + 0.799 * BF2 - 1.347 * BF3. Therefore, performance model was comprised by multilinier curve, then function model of algor mortis on ambient room be defined into three PMT intervals i.e: 1)Y=37,94 -0.11*(0-2h) (p>0.00); 2) Y = 40.88 - 1.87* (2-6h) ( p<0.00) and 3) Y=30.82-0.09*(6-22h) (p<0.00) while on 20ºC condition room, was : 1)Y = 34.78-0.09* (0-2h) (p<0.00) ; 2) Y = 37.97-2.38* (2-6h) (p<0.00) and 3)Y = 25.36-0.04* 6-22 h (p>0.00). The acceleration of the declining algor mortis at conditioning room showed steeper than on ambient room at 2-6h PMT interval (ß : 2,38 vs 1,87). Postmortem Time Interval Estimation from Algormortis Temperature of Rats could be expressed by MARS Model. The pattern model of estimation comprised by multilinear curve with splines was fitted at both of the experimental rooms. Keywords : Postmortem time interval, algor mortis, MARS model estimation